An integrative action research (IAR) on addressing the low sales volume of Emperador Distillers Inc. during COVID-19 pandemic - Domingo, Lorenz Jay O. (Animo Repository, 2020)
This Insider Action Research Addressed the Low Sales Volume in the On-Premise Sales Department of Emperador Distillers Inc. (EDI). The COVID-19 pandemic had unleashed a new era of change for businesses. Organizations have seen its effects on the sales production, supply chain and market disruptions. Businesses must navigate the financial and operational challenges of COVID-19 while rapidly addressing the needs of their people, customers and suppliers. The on-premise sales department needed to adapt with the changes on the business market. Through action research, method of inquiries and systems thinking, the action researchers decided to address the low sales performance of the on-premise sales department. Lewin’s Change Model, Sales Process Model (Kotler and Armstrong 2017), Eisenhower Matrix and the EDI’s own framework Distribution, Visibility, Activation and Relationship Building (DVAR) were used as third person frameworks to guide the action researchers in each cycle. With the integration of social selling and sales process or Business-to-Business (B2B) Virtual Sales process, Cycle 1 showed that creative ways of getting new sales can be done during COVID-19 pandemic. After a successful evaluation in Cycle 1, the action researchers continued in taking action in Cycle 2 to see more the effectiveness of the B2B Virtual Sales Process in terms of distribution, visibility, activation and relationship building. This action research resulted another framework that can help Improve the Sales Performance of the Salespeople. In a broader context, other organizations can use this action research as a reference in adding a new sales methodology in their sales management by giving importance in time management and social customer relationship management (CRM). With the use of B2B Virtual Sales process in Cycle 1 and Cycle 2, organizations could do a portfolio selling in their products and build amazing relationships to their customers.